El problema indígena chileno en 1999 - Garrido Rojas, José (Estudios Internacionales, 1999)
Since 1992 the emergence of a series of demands by ethnic groups on the continent has been appreciated. In the case of Chile, these range from the recovery of lands that would have been usurped from them, to the questioning of the country before international courts and, in some cases, claims of autonomy and / or self-government. The ethnic issue, as in other places, has appeared together with environmental demands, defense of the native forest and biodiversity. We argue that the globalization of the issue is due to the emergence of an "indigenous ethno-nationalism" that interacts with environmentalism. Assuming a wide difference in the interpretation of the past by anthropologists and historians, in this paper a review of not always known aspects of this problem is made.